Evaluation of the role of susceptibility-weighted imaging (SWI) as a new complementary sequence in routine brain MRI - Haghighi-Morad, Maryam; Sadeghi, Maryam (Novelty in Biomedicine, 2025)
Background: Susceptibility-weighted imaging (SWI), an advanced MRI technique, has a high sensitivity in detecting microvascular changes, hemorrhages, and calcifications, thereby improving the diagnosis and management of various neurological pathologies. This study evaluated the frequency of abnormal findings in SWI sequence in patients with brain pathologies referred to Loghman Hakim Hospital. Materials and Methods: This cross-sectional study was conducted on patients with various brain pathologies who underwent brain MRI with SWI sequence at Loghman Hakim Hospital from October 2021 to October 2022. The frequency of different brain pathologies in the SWI sequence was assessed. Results: A total of 157 brain pathologies were evaluated. In 129 cases (82.2%), the most probable lesion diagnosis was only found in the SWI sequence. Thrombosis in veins was found in all cerebral venous thrombosis (CVT) patients in SWI and other sequences. Hemorrhage in venous infarct was observed in 20% of CVT cases. In patients with vascular malformations, the diagnosis of cavernoma was made in 9 patients (81.8%) and capillary telangiectasia in 2 patients (18.2%). Conclusion: The findings of this study demonstrated the significant role of SWI in evaluating various brain pathologies, especially in cases where routine MRI sequences are not diagnostic. Therefore, we recommend using SWI in routine brain MRI.